Risk factors for sexual dysfunction after rectal cancer surgery in 948 consecutive patients: A prospective cohort study. Issue 8 (August 2021) - Li, Kai; He, Xiaobo; Tong, Shilun; Zheng, Yongbin
Abstract: Background: Sexual dysfunctions seriously affect the quality of life of patients. The aim of this study was to identify the risk factors for sexual dysfunction after rectal cancer surgery. Methods: A total of 948 consecutive patients undergoing rectal cancer radical resection were included between January 2012 and August 2019. The sexual functions were evaluated by the 5-item version of the International Index of Erectile Function (IIEF-5) in men and Index of Female Sexual Function (IFSF) in women at 12 months postoperatively. Results: Postoperative sexual dysfunction was observed in 228 patients with rectal cancer (24.05%), which included 150 cases in male patients (25.0%) and 78 cases in female patients (22.5%). A multivariate logistic regression analysis results showed that age ≥45 years old (OR = 1.72, p = 0.001), tumor below the peritoneal reflection (OR = 1.64, p = 0.005), receiving preoperative radiotherapy (OR = 4.12, p < 0.001) and undergoing abdominoperineal resection (APR), intersphincteric resection (ISR) and Hartmann surgery (OR = 2.43, p < 0.001) were the independent risk factors of sexual dysfunction for patients with rectal cancer. Conclusion: Age ≥45 years old, tumors below the peritoneal reflection, receiving preoperative radiotherapy, and undergoing APR, ISR and Hartmann surgery were the independent risk factors of sexual dysfunction. Patients should be informed about the sexual dysfunctions in the pre-operative consultations. More attention should be paid to intraoperative pelvic autonomic nerve preservation on rectal cancer patients with these risk factors for clinic surgeons.